Hashtag war: 2019 Presidential election rhetoric in Indonesia - Avin Fadilla Helmi; Mardhani Riasetiawan; Acintya Ratna Priwati; Itsna Mawadatta Rahma; Arlianto Arlianto; Ramadhan Dwi Marvianto; Rinanda Rizky Amalia Shaleha (Universitas Ahmad Dahlan, 2020)
Twitter as a social media has become increasingly used, including by its use by each Presidential candidate’s stronghold to launch a campaign to influence prospective voters’ electoral decisions in the 2019 Presidential Election in Indonesia. One strategy used in such a campaign on Twitter was by disseminating hashtags that were expected to become trending topics on Twitter. The dissemination of these hashtags aimed to build political rhetoric that can influence prospective voters’ electoral decisions. Thus, this study sought to explore the patterns of hashtags disseminated by each candidate’s stronghold to build political rhetoric and find out public sentiments in the posted Twitter contents. The number of tweets with #Jokowi2Periode and #2019GantiPresiden hashtags during the period of the 2019 Indonesian presidential and vice-presidential debates that were successfully downloaded using MAXQDA 18.1.1 software was 92,276. The research findings revealed that the distribution pattern of the #Jokowi2Periode hashtag tended to be more scattered (decentralized) by relying on the actor’s presentation and the actor’s speed in responding to tweets. In contrast, the spread of the #2019GantiPresiden hashtag was more centralized by relying on communication channels on Twitter. These two distribution patterns are discussed with the perspective of cyber psychology, through cuesfiltered-in and cues-filtered-out theories.